Perilaku Konsumen Terhadap Jajanan Tradisional di Kabupaten Pekalongan - Tjahja Muhandri; Uswatun Hasanah; Aisyah Amanah (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2021)
Traditional snacks are made from local ingredients, cooked by boiling, steaming, frying, or grilling, whose recipes are passed down from predecessors throughout generations. This research was aimed to study consumer behavior in Pekalongan Regency towards traditional snacks and their preferences for traditional and modern snacks. This research was conducted with a survey method using the Google form online questionnaire to 100 respondens. Consumers of traditional snacks, both men and women, came from various ages, occupations, and income groups. The most popular and most consumed traditional snacks included getuk, nagasari, risol, klepon, bolang-baling, onde-onde, rengginang, rempeyek, putu, arem-arem, and apem. The majority of consumers bought traditional snacks at markets, street vendors, and food stalls. As many as 49% of consumers often consumed traditional snacks with a frequency of 1-7 times a week. As many as 79% of consumers from various age groups preferred traditional snacks because of its delicious and unique taste, affordable prices, natural ingredients, no preservatives, and preserving culture. As many as 29.51% of young consumers (≤ 25 years old) preferred modern snacks due to the simplicity, variations, easiness to get, attracti-veness, and hygienic.